Hotter and Weaker Mediterranean Outflow as a Response to Basin-Wide Alterations - García-Lafuente, Jesús; Sammartino, Simone; Huertas, I. Emma; Flecha, Susana; Sánchez-Leal, Ricardo F.; Naranjo, Cristina; Nadal, Irene; Bellanco, María Jesús (Frontiers in Marine Science, 2021)
Time series collected from 2004 to 2020 at an oceanographic station located at the westernmost sill of the Strait of Gibraltar to monitor the Mediterranean outflow have been used to give some insight on changes that could have been taking place in the Mediterranean basin. Velocity data indicate that the exchange through the Strait is submaximal with a mean value of -0.847±0.129 Sv and a slight trend to decrease in magnitude (+0.017±0.003 Sv decade-1). Submaximal exchange promotes footprints in the Mediterranean outflow with little or no-time delay with regards to changes occurring in the basin. An astonishing warming trend of 0.339±0.008ºC decade-1 in the deepest layer of the outflow from 2013 onwards stands out among these changes, a trend that is an order of magnitude greater than any other reported so far in the water masses of the Mediterranean Sea. Biogeochemical (pH) data display a negative trend indicating a gradual acidification of the outflow in the monitoring station. Data analysis strongly suggests that these trends are the result of a progressively larger participation of Levantine Intermediate Water (slightly warmer and more acidic than the Western Mediterranean Deep Water) in the outflow. Climatic data (ERA-5 reanalysis) indicate diminished buoyancy fluxes to the atmosphere during last seven years, which would have reduced the rate of formation of Western Mediterranean Deep Water, a fact right away echoed by the outflow through the Strait in a situation of submaximal exchange that is ultimately reflected in the shocking temperature trend recorded at the monitoring station.